TYPICAL AND ATYPICAL PRESENTATION OF COVID-19 INFECTION IN CHILDREN IN THE TOP OF PANDEMIC IN MINIA GOVERNORATE (TWO CENTER EXPERIENCE) - Madeha Abdalla Sayed; Mohamed Abdelhakeem (Mediterranean Journal of Hematology and Infectious Diseases)
Back ground: A novel coronavirus which is identified as cause of pandemic situation inFebruary2020 and affecting adult and children with variable presentation and outcome.